2011
DOI: 10.3141/2265-07
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Motorcycle Crashes in Texas with Multinomial Logit Model

Abstract: 62and motorcyclist fatalities increased by 31% (from 407 to 530) during the same period of time.Motorcyclists represent the most vulnerable of road users and are particularly susceptible to being seriously injured if involved in a crash. From 2003 through 2008, motorcycle injuries increased from 6,061 to 9,708 (60%). Motorcyclists made up 4% of all traffic-related crash injuries in 2008, doubling from 2% in 2003.Multiple factors contribute to motorcyclists' crash and injury severity including speeding, alcohol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
52
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(60 citation statements)
references
References 18 publications
6
52
0
2
Order By: Relevance
“…Geedipally et al . [54] investigated motorcycle crash severity in Texas, USA, using a multinomial logit model. Other numerous studies that used multinomial in their studies include Shaheed et al .…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Geedipally et al . [54] investigated motorcycle crash severity in Texas, USA, using a multinomial logit model. Other numerous studies that used multinomial in their studies include Shaheed et al .…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, the settlement type: such as city, town, or rural; also affects motorcycle crash severity [26,29,31,61,67]. Previous studies discovered that the location of the crash: such as the intersection; was associated with the increasing severity of motorcycle crashes [55,61,70,72], while others found that the road description was related to injury severity [31,54,57,59,63,72].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The benefit of using MNL is that each injury outcome has an individual function while the ordered model has the same coefficient of the same variable for the injury outcomes. It is likely that the ordered model might overestimate the probability of the high injury level while underestimates the low injury level [7]. Moreover, the same variable might significantly impact one injury level and not the other one.…”
Section: Methologymentioning
confidence: 99%
“…Except for the abovementioned mathematical models, other models used for accident analysis include ordered logit models, [8][9][10] multinomial logit, or probit models. 11,12 However, these statistical methods consider all factors to be independent rather than related. In reality, multiple factors contribute to serious multi-fatality crashes and these factors are often interrelated.…”
Section: Introductionmentioning
confidence: 99%